2012
DOI: 10.1186/1746-4269-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge and socio-economic determinants of traditional medicines' utilization in livestock health management in Southwest Nigeria

Abstract: Smallholder livestock farmers in Nigeria utilize traditional medicines derived from medicinal plants (PMs) for the maintenance of their animals' health. This study was designed to determine the PMs used in the study area and their level of utilization by livestock farmers, compare the level of utilization of PMs across the three states surveyed and identify the socio-economic factors influencing farmer's utilization of PMs. Thirty-five PMs were identified. Farmers had considerable knowledge about the identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 8 publications
3
14
0
1
Order By: Relevance
“…Many people generally prefer the dual effect of "spiritual and physiological treatment" offered by TM compared with that from conventional medicines [20]. This corroborates findings by WHO [14], Mafimisebi and Oguntade [13], Mafimisebi and Oguntade [28] and Mafimisebi et al [18] for Nigeria It is estimated that the conventional medicines industry of South Africa is worth about USD 415 million. It also constitutes around 5.6% of the nation's total health budget.…”
Section: South Africasupporting
confidence: 73%
See 1 more Smart Citation
“…Many people generally prefer the dual effect of "spiritual and physiological treatment" offered by TM compared with that from conventional medicines [20]. This corroborates findings by WHO [14], Mafimisebi and Oguntade [13], Mafimisebi and Oguntade [28] and Mafimisebi et al [18] for Nigeria It is estimated that the conventional medicines industry of South Africa is worth about USD 415 million. It also constitutes around 5.6% of the nation's total health budget.…”
Section: South Africasupporting
confidence: 73%
“…Traditional herbal remedies are staging a comeback as popular alternatives to chemical medicines in many developed countries. The demand for high quality, certified, and/or organic herbal products is increasing with one of the consequences being unsustainable harvesting of MPs and other forest products [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The sizes of livestock herd, land owned, and family member were slightly correlated (household~land 0.38, household~livestock 0.41, and land~livestock 0.48). Larger families own larger herds [ 95 , 133 ] which is important for the transhumance community [ 134 ]. Household size increases brought about an increased utilization of medicinal plants, perhaps due to economic pressure in larger families.…”
Section: Discussionmentioning
confidence: 99%
“…When there is lack of experience, the likely outcomes have been shown to be low income for marketers. (Mafimisebi et al, 2012). The result in Table 1 also showed that the household size of 1-5 persons was recorded for 70% of the respondents while 6-10 persons were recorded for 30% of the respondents.…”
Section: Socio-economic Characteristics Of the Respondentsmentioning
confidence: 80%